Rapid detection of the red fire ant Solenopsis invicta (Hymenoptera: Formicidae) by loop-mediated isothermal amplification - Nakajima, Nobuyoshi; Sakamoto, Yoshiko; Goka, Koichi (Applied Entomology and Zoology, 2019)
We developed a loop-mediated isothermal amplification (LAMP) assay to detect the red imported fire ant, Solenopsis invicta Buren, an invasive species in Japan. We designed species-specific LAMP primers on the basis of the nucleotide sequence of the S. invicta mitochondrial cytochrome c oxidase subunit 1 region. The system we developed has a sensitivity and specificity enabling detection of one S. invicta in a mixed sample including nine individuals of a non-target ant species. We were easily able to detect the S. invicta DNA visually based on the turbidity of the reaction mixture. This rapid and easy LAMP assay system provides a powerful tool for the early detection and identification of S. invicta in invaded regions.